2020
DOI: 10.1186/s12979-020-00206-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen burden and leukocyte telomere length in the United States

Abstract: Background Prior studies in humans have suggested that telomere shortening may be accelerated by infection, but research on multiple pathogens and use of large population-based study samples has been limited. We estimated cross-sectional associations between seropositivity to five persistent pathogens (Herpes Simplex Virus Type-1 (HSV-1), Herpes Simplex Virus Type-2 (HSV-2), cytomegalovirus (CMV), Helicobacter pylori (H.pylori), and Hepatitis B) as well as total pathogen burden and leukocyte telomere length. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Since then, an explosion of literature has shown associations between telomere length, as measured in the blood, and various human diseases in observational studies, leading to many meta-analyses showing small but consistent correlations. The list includes major diseases such as cardiovascular diseases ( Yeh and Wang, 2016 ), diabetes and metabolic syndrome ( Cheng et al, 2020 ), COPD and idiopathic pulmonary fibrosis ( Birch et al, 2018 ), infection (including COVID-19) ( Noppert et al, 2020 ; Asghar et al, 2018 , 2016 ; Helby et al, 2017 ; Bellon and Nicot, 2017 ; Froidure et al, 2020 ; Sanchez-Vazquez et al, 2021 ), psychological disorders ( Epel and Prather, 2018 ), autoimmune diseases ( Habib et al, 2020 ; Kamycheva et al, 2017 ; Zeng et al, 2020 ), and some types of cancers ( Zhang et al, 2017 ; Zhu et al, 2016 ). Observational studies have been inconsistent with regard to the direction of effect for different types of cancers.…”
Section: Telomere Length and Diseasementioning
confidence: 99%
“…Since then, an explosion of literature has shown associations between telomere length, as measured in the blood, and various human diseases in observational studies, leading to many meta-analyses showing small but consistent correlations. The list includes major diseases such as cardiovascular diseases ( Yeh and Wang, 2016 ), diabetes and metabolic syndrome ( Cheng et al, 2020 ), COPD and idiopathic pulmonary fibrosis ( Birch et al, 2018 ), infection (including COVID-19) ( Noppert et al, 2020 ; Asghar et al, 2018 , 2016 ; Helby et al, 2017 ; Bellon and Nicot, 2017 ; Froidure et al, 2020 ; Sanchez-Vazquez et al, 2021 ), psychological disorders ( Epel and Prather, 2018 ), autoimmune diseases ( Habib et al, 2020 ; Kamycheva et al, 2017 ; Zeng et al, 2020 ), and some types of cancers ( Zhang et al, 2017 ; Zhu et al, 2016 ). Observational studies have been inconsistent with regard to the direction of effect for different types of cancers.…”
Section: Telomere Length and Diseasementioning
confidence: 99%
“…They maintain a persistent infection by manipulating diverse aspects of host immune function [ 32 ]. The ensuing background level of multiple layers of immune manipulation have been linked to chronic mental and physical diseases including autoimmunity [ 33 , 34 , 35 , 36 , 37 ], increased speed of ageing [ 38 , 39 , 40 , 41 ], and chronic inflammation [ 42 ]. Pathogen burden is highest among the most disadvantaged social groups [ 43 ]—who also experience lower lifespan.…”
Section: A Wider Context To Pathogen Interferencementioning
confidence: 99%
“…Recent evidence has suggested that infections with certain combinations of pathogens may decisively contribute to accelerated cellular senescence, possibly beginning early in life. Thus, chronic inflammatory responses secondary to a range of persistent pathogens may have a major impact on markers of cellular aging such as TL [169]. However, the relevance of coinfections and latent pathogen burden in onset and severity of MS remains largely unexplored.…”
Section: Other Infectionsmentioning
confidence: 99%